Застосування інформаційних технологій при підготовці вчителя іноземної мови у контексті інтеграції до європейського освітнього простору - Околович, Олександр (Studies in Comparative Education, 2015)
У статті викладено деякі підходи організації процесу вивчення іноземної мови в умовах застосування нових інформаційних технологій. Проаналізовано чинники вербальної комунікації, передумови навчання усного мовлення вищого комунікативного рівня, впровадження інформаційних технологій у педагогічну теорію та практику. Висвітлено наукові підходи до організації самостійної роботи студентів факультетів іноземних мов, зростання вимог до рівня професійної компетентності та основні педагогічні, методичні, технологічні умови їх реалізації. Розглянуто специфіку організації навчального процесу та творчої діяльності студентів мовних спеціальностей в умовах інтеграції до європейського освітнього простору. В статье освещены некоторые подходы к организации процесса изучения иностранных языков в условиях применения новых информационных технологий. Проанализированы факторы вербальной коммуникации, предпосылки обучения устной речи высшего коммуникативного уровня, внедрения информационных технологий в педагогическую теорию и практику. Освещены научные подходы организации самостоятельной работы студентов факультетов иностранных языков, повышение требований к уровню профессиональной компетентности и основные педагогические, методические, технологические условия их реализации. Рассмотрена специфика организации учебного процесса и творческой деятельности студентов филологических специальностей в условиях интеграции в европейское образовательное пространство. In the article certain methods regarding foreign language study process in application conditions of the new information technologies are discussed. The factors of the verbal communication, premises of the verbal communication teaching at the higher level, introduction of information technologies in the pedagogical theory and practice are considered. The scientific approaches to the organization of the independent foreign-language students’ work, increasing demands to the level of professional competence and the main pedagogical, methodical and technological conditions of their realization are considered. The peculiarities of study process organization and creative activity of linguistic profession students under integration into the European educative space are shown. European norms demand forming in Ukraine the system of the open state informational resources which contains following sub-systems: leading, normative and legislative, organization and methodical, executive (centers certifying electronic notarial system, quality and arbitration). One of the increasing sources of the effectiveness of the state educational policy is the availability in the country the developed national and the transnational database resources. The Internet system enables interconnection between the countries, organizations and separate persons. The quick technological progress of the work with video on computer and transmission of the video information into the computer net gave a push to the new possibilities of the video technologies use in education and foreign language learning. Teachers belong to the special consumers of the information resources, because information is the only one and unique channel of their communication with the world society. Satisfaction of the need of information in education foresees a process of an intensive penetration of knowledge into the life of a separate person and society in general on the base of transformation of knowledge into the information resource like information materialized knowledge. Information communicative technologies, especially its automatized treatment, are a very important factor of the educational management in quality increase and state policy of education. The Ministry of science and education of Ukraine is showing activity in this range: creates an educational network, organizes stable paperwork document control in the sphere of education etc. Foreign language should be learned as a specific activity, which provides production and perception of the foreign language expressions, readiness of the entry to the real conversation in the conditions of integration into the European educational society.